Hydroxyethylamine based analog targets microtubule assembly: an in silico study for anti-cancerous drug development - Pawan Kumar; Rajni Khan; Basant Narain Singh; Anisha Kumari; Ankit Rai; Anil Kumar Singh; Amresh Prakash; Shashikant Ray (Scientific Reports, 2024)
Abstract Microtubules are dynamic cytoskeletal structures essential for cell architecture, cellular transport, cell motility, and cell division. Due to their dynamic nature, known as dynamic instability, microtubules can spontaneously switch between phases of growth and shortening. Disruptions in microtubule functions have been implicated in several diseases, including cancer, neurodegenerative disorders such as Alzheimer’s and Parkinson’s disease, and birth defects. The role of microtubules during various phases of the cell cycle, particularly in cell division, makes them attractive targets for drug development against cancer. Several successful drugs currently on the market are designed to target microtubules. However, the presence of cellular toxicity and the development of multidrug resistance necessitate the search for new microtubule-targeting drugs.Here, a library of 106 biologically active compounds were screened to identify potent microtubule assembly inhibitors. Out of all the screened compounds, the hydroxyethylamine (HEA) analogues are found to be the best hit.We identified three inhibitors, BKS3031A, BKS3045A and BKS3046A, that bind at the same site as the well-known microtubule targeting agent colchicine. These inhibitors were simulated for 100 ns with tubulin complexes, and the results indicated that they remain stable within the binding pocket of α-β tubulin complexes. In addition, we estimated the binding free energy of BKS3031A, BKS3045A and BKS3046A by using molecular mechanics generalized Born surface area (MM-GBSA) calculations, and it was found to be -32.67 ± 6.01, -21.77 ± 5.12 and − 22.92 ± 5.09 kcal/mol, respectively. Our findings suggest that these novel inhibitors have potential to bind and perturb the microtubule network, positioning them as promising microtubule-targeting agents.